2010
DOI: 10.2460/ajvr.71.7.799
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of gemcitabine against canine osteosarcoma cell lines in vitro

Abstract: Gemcitabine exhibited biological activity against canine OSA cell lines in vitro, and a combination of gemcitabine and carboplatin exhibited synergistic activity at biologically relevant concentrations. Findings support future clinical trials of gemcitabine alone or in combination with carboplatin for the treatment of dogs with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…15 In this study, the IC50 for gemcitabine alone ranged from 5.7 to 15.3 μM for all OSA cell lines tested and the combination index indicated strong synergism at 1 μM gemcitabine/100 μM carboplatin. Based on the previous study evaluating the administration of carboplatin/gemcitabine to dogs, the recommended dosage of gemcitabine to be used with carboplatin was 2 mg/kg.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…15 In this study, the IC50 for gemcitabine alone ranged from 5.7 to 15.3 μM for all OSA cell lines tested and the combination index indicated strong synergism at 1 μM gemcitabine/100 μM carboplatin. Based on the previous study evaluating the administration of carboplatin/gemcitabine to dogs, the recommended dosage of gemcitabine to be used with carboplatin was 2 mg/kg.…”
mentioning
confidence: 61%
“…28 In our preclinical work, we demonstrated that that addition of gemcitabine to carboplatin resulted in synergistic inhibition of OSA cell viability in vitro and found that growth inhibition was greater in 3/4 canine OSA cell lines when they were treated with carboplatin 4 hours before gemcitabine rather than with gemcitabine 4 hours before carboplatin. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All cells were maintained at 37°C in a humidified 5% CO 2 atmosphere. The following additional canine tumor cell lines were used to evaluate response to SINE compounds: C2, mast cell tumor line provided by Dr. George Caughey, UCSF, San Francisco, CA [33]; OSA16, osteosarcoma cell line, provided by Dr. Jaime Modiano, UM, Minneapolis, MN [34]; and 323610-3, malignant melanoma cell line, provided by Dr. Michael Kent, UCD, Davis, CA [35]. All cell lines were cultured in complete RPMI media containing 10% FBS, antibiotic/antimycotic, HEPES, sodium pyruvate, nonessential amino acids and Glutamax (media supplements from Gibco).…”
Section: Methodsmentioning
confidence: 99%